The New Testament in color : a multiethnic Bible commentary - McCaulley, Esau; Ok, Janette H.; Padilla, Osvaldo; Peeler, Amy L. B. (Downers Grove, IL : IVP Academic, 2024)
"In this one-volume commentary, a multiethnic team of scholars holding orthodox Christian beliefs brings exegetical expertise coupled with a unique interpretive lens to illuminate the ways social location and biblical interpretation work together. These diverse scholars offer a better vantage point for both the academy and the church"--
"Historically, Bible commentaries have focused on the particular concerns of a limited segment of the church, all too often missing fresh questions and perspectives that are fruitful for biblical interpretation. Listening to scholars from diverse backgrounds and ethnicities offers us an opportunity to explore the Bible from a wider angle, a better vantage point.The New Testament in Color is a one-volume commentary on the New Testament written by a multiethnic team of scholars holding orthodox Christian beliefs. Each scholar brings exegetical expertise coupled with a unique interpretive lens to illuminate the ways social location and biblical interpretation work together. Theologically orthodox and multiethnically contextual, The New Testament in Color fills a gap in biblical understanding for both the academy and the church. Who we are and where God placed us-it's all useful for better understanding his Word"--
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries; RELIGION / Biblical Commentary / New Testament / General; RELIGION / Biblical Studies / New Testament / General; Commentaries